Chemical control of spin–lattice relaxation to discover a room temperature molecular qubit. Issue 23 (30th May 2022) - Amdur, M. Jeremy; Mullin, Kathleen R.; Waters, Michael J.; Puggioni, Danilo; Wojnar, Michael K.; Gu, Mingqiang; Sun, Lei; Oyala, Paul H.; Rondinelli, James M.; Freedman, Danna E.
Abstract : Elucidating the role of specific vibrational modes in spin lattice relaxation is a key step to designing room temperature qubits. We executed an experimental and theoretical study on a series of Cu 2+ qubits to increase their operating temperature. Abstract : The second quantum revolution harnesses exquisite quantum control for a slate of diverse applications including sensing, communication, and computation. Of the many candidates for building quantum systems, molecules offer both tunability and specificity, but the principles to enable high temperature operation are not well established. Spin–lattice relaxation, represented by the time constant T 1, is the primary factor dictating the high temperature performance of quantum bits (qubits), and serves as the upper limit on qubit coherence times ( T 2 ). For molecular qubits at elevated temperatures (>100 K), molecular vibrations facilitate rapid spin–lattice relaxation which limits T 2 to well below operational minimums for certain quantum technologies. Here we identify the effects of controlling orbital angular momentum through metal coordination geometry and ligand rigidity via π-conjugation on T 1 relaxation in three four-coordinate Cu 2+ S = ½ qubit candidates: bis( N, N ′-dimethyl-4-amino-3-penten-2-imine) copper(ii ) (Me2 Nac)2 (1 ), bis(acetylacetone)ethylenediamine copper(ii ) Cu(acacen) (2 ), and tetramethyltetraazaannulene copper(ii ) Cu(tmtaa) (3 ). We obtain significant T 1 improvement upon changing from tetrahedral to square planar geometries through changes in orbital angular momentum. T 1 is further improved with greater π-conjugation in the ligand framework. Our electronic structure calculations reveal that the reduced motion of low energy vibrations in the primary coordination sphere slows relaxation and increases T 1 . These principles enable us to report a new molecular qubit candidate with room temperature T 2 = 0.43 μs, and establishes guidelines for designing novel qubit candidates operating above 100 K.